2015
DOI: 10.1186/s12884-015-0655-4
|View full text |Cite
|
Sign up to set email alerts
|

Fear of childbirth and elective caesarean section: a population-based study

Abstract: BackgroundThis population-based cohort study aimed to investigate the demographic and psychosocial characteristics associated with fear of childbirth and the relative importance of such fear as a predictor of elective caesarean section.MethodsA sample of 1789 women from the Akershus Birth Cohort in Norway provided data collected by three self-administered questionnaires at 17 and 32 weeks of pregnancy and 8 weeks postpartum. Information about the participants’ childbirths was obtained from the hospital records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
130
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(153 citation statements)
references
References 63 publications
14
130
0
6
Order By: Relevance
“…Fear of delivery is one of the factors that leads to caesarean. This is verified by the study conducted by Storksen et al (19). The results of their study showed that 80% of their participants were afraid of delivery, and, although this fear was related to elective caesarean and caesarean section, the majority of their participants did not go under caesarean operation.…”
Section: Discussionsupporting
confidence: 81%
“…Fear of delivery is one of the factors that leads to caesarean. This is verified by the study conducted by Storksen et al (19). The results of their study showed that 80% of their participants were afraid of delivery, and, although this fear was related to elective caesarean and caesarean section, the majority of their participants did not go under caesarean operation.…”
Section: Discussionsupporting
confidence: 81%
“…These pregnancy-related anxieties are not associated with general anxiety or depressive feelings,177 and are reported by 14.4% of pregnant women 178. Fear of giving birth has been reported by 8% of women in a general pregnant population 179. Whether athletes suffer more or less from pregnancy-related anxieties is unknown, but they might have anxieties about being able to return to their sporting career, in the same way as some women have anxiety about returning to work 180…”
Section: Pregnancymentioning
confidence: 99%
“…Moreover, in the second counseling session, if the last delivery was cesarean section was accompanied by higher success rate than if it was not, p<0.001. As a result, the only explanation could be secondary tokophobia which is known as fear of labor pain or getting normal childbirth due to last pregnancy experience [24][25][26]. If patients are worried from pain or about the fetus, they can express their fears and we can release their concerns.…”
Section: Discussionmentioning
confidence: 99%